6p+5q-7(6p-3q+7r)=

Simple and best practice solution for 6p+5q-7(6p-3q+7r)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+5q-7(6p-3q+7r)= equation:


Simplifying
6p + 5q + -7(6p + -3q + 7r) = 0
6p + 5q + (6p * -7 + -3q * -7 + 7r * -7) = 0
6p + 5q + (-42p + 21q + -49r) = 0

Reorder the terms:
6p + -42p + 5q + 21q + -49r = 0

Combine like terms: 6p + -42p = -36p
-36p + 5q + 21q + -49r = 0

Combine like terms: 5q + 21q = 26q
-36p + 26q + -49r = 0

Solving
-36p + 26q + -49r = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-26q' to each side of the equation.
-36p + 26q + -26q + -49r = 0 + -26q

Combine like terms: 26q + -26q = 0
-36p + 0 + -49r = 0 + -26q
-36p + -49r = 0 + -26q
Remove the zero:
-36p + -49r = -26q

Add '49r' to each side of the equation.
-36p + -49r + 49r = -26q + 49r

Combine like terms: -49r + 49r = 0
-36p + 0 = -26q + 49r
-36p = -26q + 49r

Divide each side by '-36'.
p = 0.7222222222q + -1.361111111r

Simplifying
p = 0.7222222222q + -1.361111111r

See similar equations:

| 7/8(p)=-16/4 | | x*2+8x-9=0 | | 4u+2v-2(4u-7v+3w)= | | x^2+4x^2-32x=0 | | 8/9-5m/9=14/9 | | x-6/7=23 | | 12=13/4x-10 | | 1/2-2/3x=5 | | 4-5(y+3)+6y=7 | | 2(3x-4)=3(2x+1)-11 | | 1/1/k | | 16v-81v^3= | | y=-3/2*2-3 | | y=-3/2*3-3 | | 49y^2+42y+9= | | y=-7/10(-7)+7 | | 1/3y-1/4y=1/y^2 | | 78.1%147= | | 2x-9=7x+4 | | 10x^2+6x-99=0 | | 10x^2+6x-99=100 | | 4y^2+3/2y-2=0 | | 7x^2-5=100 | | 235-5x=40x+20 | | 21p+52=10 | | 5/(2w+12)+1=-8/(w+6) | | 3x+36=10x-41# | | 7/w-2=-8+(5/w+1) | | 6x/x+1+2/x-3=6 | | 12r+24=-12 | | x^2-5x+22=0 | | 16-9u=20 |

Equations solver categories